3D DOCUMENTATION OF CULTURAL HERITAGE USING TERRESTRIAL LASER SCANNING - Llabani, Arli; Abazaj, Freskida (Journal of Applied Engineering Science, 2024)
This study presents a comprehensive exploration of the application of terrestrial laser scanning (TLS) technology for the 3D documentation of cultural heritage, focusing on the iconic Clock Tower of Tirana as a case study. Terrestrial laser scanning has emerged as a powerful tool in the field of cultural heritage preservation, offering a non-intrusive and highly accurate method for capturing the intricate details of historical structures. The research employs state-of-the-art TLS equipment to create a detailed 3D model of the Clock Tower, a prominent cultural landmark in Tirana, Albania. The methodology involves scanning the exterior of the tower, capturing its architectural features, ornate decorations, and historical elements. The high precision of TLS facilitates the generation of a point cloud, enabling the creation of an accurate digital replica that serves as a valuable resource for conservation, research, and education. The study also explores the challenges and benefits associated with TLS technology in the context of cultural heritage documentation. Issues such as data processing, registration, and integration of multiple scans are addressed, emphasizing the importance of a meticulous approach to ensure the reliability of the 3D model. Additionally, the research highlights the potential of the digital model in supporting conservation efforts, risk assessment, and virtual tourism, promoting accessibility and understanding of cultural heritage for a wider audience. The findings of this study contribute to the growing body of knowledge on 3D documentation techniques for cultural heritage preservation and provide insights into the specific application of terrestrial laser scanning in the context of the Clock Tower of Tirana. The results underscore the significance of leveraging advanced technologies to safeguard and promote the rich cultural heritage embedded in historical structures, fostering a deeper appreciation for the past while ensuring its preservation for future generations